ANALISIS KINERJA KANTOR PERTANAHAN KOTA SEMARANG DALAM PELAYANAN SERTIFIKASI TANAH - Iqmalia Soraya Dwisandhi; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2019)
Semarang City Land Office is a public organization that has complaints about public services in land certification services. Against this background, the purpose of this study is to analyze the performance of the Semarang City Land Office in land certification services assessed in terms of productivity, service quality, responsiveness , and accountability as well as knowing what are the factors that hamper the performance of the Semarang City Land Office in the land certification service as seen from the human resources and organizational culture. This study uses descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. The results of this study, the performance of the Semarang City Land Office in land certification services has not been running optimally because of not achieving targets on time, unclear procedures, time and cost in land certification services, and the availability of human resources that are lacking, and poor organizational culture . Recommendations that can be given based on the results of the research are that there is a need for performance evaluation by delegating tasks to employees, there is socialization and work guidelines in providing services to the public in accordance with SOP, updating reports up to date on the website as a form of openness of the Semarang City Land Office , adding new employees and controlling employees, as well as emphasizing the attitude of character revolution for Semarang City Land Office employees, which is expected to realize good governance.